Direct formation of wafer-scale single-layer graphene films on the rough surface substrate by PECVD. (April 2018) - Guo, Liangchao; Zhang, Zhenyu; Sun, Hongyan; Dai, Dan; Cui, Junfeng; Li, Mingzheng; Xu, Yang; Xu, Mingsheng; Du, Yuefeng; Jiang, Nan; Huang, Feng; Lin, Cheng-Te
Abstract: The technical advance of plasma enhanced chemical vapor deposition (PECVD) exhibits the potential to grow large-area high-quality graphene films at relatively low growth temperature, which is beneficial to the fabrication of graphene-based electronic devices/sensors and transparent electrode. However, it remains a challenge to overcome the degradation of graphene quality during growth by PECVD, due to the continuous bombardment of plasma ions on the catalyst surface. Herein, the combined techniques of PECVD and the growth of graphene underneath the catalyst layer were proposed. As a result, transfer-free single-layer graphene films with 2.5 inch in diameter on quartz substrate can be obtained with the growth temperature of 700 °C, which is 250 °C lower than that for graphene synthesis using thermal CVD. The graphene films prepared by our method show the ability to form on the rough surfaces with millimeter-scale grooves and have minimal surface contamination, compared to that of conventionally transferred CVD graphene. Graphical abstract: Image 1